TINGKAT KEBISINGAN AKIBAT AKTIVITAS LALU LINTAS YANG BERADA DI KAWASAN PASAR LASOANI KOTA PALU - Mohamad Rifki Abdi; Andi Iin Nindy Karlinda Kadir; Siti Nurfajrina J. Patunrangi; Aristi Ayuningsi Ode Asri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2025)
Rapid population growth in urban areas affects various aspects of life, including population mobility and changes in socio-economic activities. One of the negative impacts resulting from these changes is the increase in noise levels, which becomes a significant source of sound pollution in urban environments. This study aims to identify the traffic noise levels generated by activities at Pasar Lasoani, Palu City, and analyze the factors influencing them, such as vehicle volume and vehicle speed. The methods used in this study include noise measurement, traffic volume analysis, vehicle speed measurement, and multiple linear regression analysis. The results show that the noise levels at Pasar Lasoani on Saturday exceeded the environmental quality standards, with noise levels at monitoring points reaching 74 dB. On Monday, when there was no market activity, the noise levels were lower. Vehicle volume and speed were found to have a significant impact on noise levels, with vehicle volume having a positive effect and vehicle speed having a negative effect on noise levels. The multiple linear regression analysis indicated that vehicle volume (X1) and vehicle speed (X2) significantly influence noise levels simultaneously. Noise distribution mapping using Surfer 11 software showed variations in noise levels at different points in the Pasar Lasoani area, with the highest noise levels occurring on Saturday. This study provides a clear understanding of the factors influencing noise levels and noise distribution in crowded market areas, as well as the contribution of economic activities to urban environmental quality.